Faktor Risiko Shoulder Sprain Terhadap Pemanen Kelapa Sawit Yang Berhubungan Dengan Ergnomis Di Desa Namu Ukur Kabupaten Langkat - Rifki Abdillah; Herbert Wau; Hartono (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Background: Shoulder sprain is a ligament injury of the shoulder joint resulting from repetitive work activities, non-ergonomic postures, and heavy lifting. Oil palm harvesters represent a high-risk group for this injury because harvesting is performed manually using long-handled tools with the hands raised above shoulder level repeatedly. Musculoskeletal disorder prevalence in the plantation sector continues to rise, and shoulder-specific injuries remain understudied. Objective: This study aimed to analyze the relationship between ergonomic factors (work posture, workload, length of employment, and work duration) and the incidence of shoulder sprain among oil palm harvesters in Namu Ukur Village, Langkat Regency, 2026. Methods: A quantitative cross-sectional study was conducted. The population comprised all 30 oil palm harvesters in the study village, selected via total sampling. Data were collected using REBA for posture assessment, observation sheets for workload, questionnaires for work duration and employment length, and the Nordic Body Map for shoulder sprain detection. Data were analyzed using Chi-Square test (α = 0.05). Results: Twenty respondents (66.7%) experienced shoulder sprain. Significant associations were found between work posture (p=0.017), workload (p=0.007), length of employment (p=0.045), and work duration (p=0.000) with shoulder sprain incidence. Conclusion: All examined ergonomic factors were significantly associated with shoulder sprain. Comprehensive ergonomic interventions including posture training, workload reduction, job rotation, and provision of more ergonomic harvesting tools are recommended to reduce shoulder injury prevalence among oil palm harvesters.